2017
DOI: 10.1021/acsnano.6b06089
|View full text |Cite
|
Sign up to set email alerts
|

Atomic H-Induced Mo2C Hybrid as an Active and Stable Bifunctional Electrocatalyst

Abstract: Mo 2 C nanocrystals (NCs) anchored on vertically aligned graphene nanoribbons (VA-GNR) as hybrid nanoelectrocatalysts (Mo 2 C-GNR) are synthesized through the direct carbonization of metallic Mo with atomic H treatment. The growth mechanism of Mo 2 C NCs with atomic H treatment is discussed. The Mo 2 C-GNR hybrid exhibits highly active and durable electrocatalytic performance for the hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). For HER, in an acidic solution the Mo 2 C-GNR has an onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 59 publications
8
91
0
Order By: Relevance
“…68 As the vital element for the synthesis of TMCs and the typical byproduct, carbon allotropes are widely used as supporting materials for HER. [69][70][71] Figure 7B showed that the F 3 W 3 C NRs were grown on both side of rGO, constructing a sandwichlike structure. The high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of Fe 3 W 3 C NRs/rGO exhibited the 1D Fe 3 W 3 C NRs with the thickness of~10 nm ( Figure 7C).…”
Section: Transition Metal Carbides/rgo-based Electrocatalystsmentioning
confidence: 99%
“…68 As the vital element for the synthesis of TMCs and the typical byproduct, carbon allotropes are widely used as supporting materials for HER. [69][70][71] Figure 7B showed that the F 3 W 3 C NRs were grown on both side of rGO, constructing a sandwichlike structure. The high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of Fe 3 W 3 C NRs/rGO exhibited the 1D Fe 3 W 3 C NRs with the thickness of~10 nm ( Figure 7C).…”
Section: Transition Metal Carbides/rgo-based Electrocatalystsmentioning
confidence: 99%
“…Carbon-based materials show a number of excellent physical and chemical properties, such as good electronic optical and mechanical properties. The carbon materials receiving most attention recently include graphene (G), [130,131] carbon nanotubes (CNTs), [132] mesoporous carbon, [66] etc. The carbon materials receiving most attention recently include graphene (G), [130,131] carbon nanotubes (CNTs), [132] mesoporous carbon, [66] etc.…”
Section: Mxene-carbon Compositesmentioning
confidence: 99%
“…led to substantial research on graphene-based composites. [99] This composite can be synthesized by an in situ growth method [130] or ex situ mixing method. For example, in graphene/nanoparticle composites, the inserted nanoparticles are able to prevent the stacking of graphene nanofilms without decreasing the large surface area or diminishing their electrical properties.…”
Section: Mxene-graphene Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, remarkable advances have been made regarding the use of transition metals and their carbides, borides, phosphides, nitrides and chalcogenides, due to their high activity, outstanding stability and earth abundance . Among these transition metal compounds, molybdenum carbide (Mo 2 C) has distinctive merits of noble‐metal‐like electronic configuration, high electronic conductivity, wide pH applicability, more importantly outstanding HER activity and stability .…”
Section: Introductionmentioning
confidence: 99%